2018
DOI: 10.1111/mec.14457
|View full text |Cite
|
Sign up to set email alerts
|

Host miRNAs are involved in hormonal regulation of HaSNPV‐triggered climbing behaviour in Helicoverpa armigera

Abstract: Baculoviruses manipulate host climbing behaviour to ensure that the hosts die at elevated positions on host plants to facilitate virus proliferation and transmission, which is a process referred to as tree-top disease. However, the detailed molecular mechanism underlying tree-top disease has not been elucidated. Using transcriptome analysis, we showed that two hormone signals, juvenile hormone (JH) and 20-hydroxyecdysone (20E), are key components involved in HaSNPV-induced tree-top disease in Helicoverpa armig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 50 publications
0
32
0
Order By: Relevance
“…In H. armigera , 20E and JH are involved in the control of climbing behaviors of single nucleopolyhedrovirus ( HaSNPV ) infected larvae. Methoprene treatment decreases expression of Br-C Z2 and increases expression of these miRNAs miR-8 and miR-429 which could target Br-C Z2 ( Zhang S. et al, 2018 ), implying the miRNA-mediated crosstalk between 20E and JH.…”
Section: Microrna Regulations On Sesquiterpenoidsmentioning
confidence: 99%
“…In H. armigera , 20E and JH are involved in the control of climbing behaviors of single nucleopolyhedrovirus ( HaSNPV ) infected larvae. Methoprene treatment decreases expression of Br-C Z2 and increases expression of these miRNAs miR-8 and miR-429 which could target Br-C Z2 ( Zhang S. et al, 2018 ), implying the miRNA-mediated crosstalk between 20E and JH.…”
Section: Microrna Regulations On Sesquiterpenoidsmentioning
confidence: 99%
“…Furthermore, involvement of Pigment-dispersing factors (PDFs) widely distributed and coexisted with per in insect optic lobes and brain are found to be actively involved in regulating the locomotor activity in drosophila and cricket, Teleogryllus commodus 34 , 35 as well as in various complex behavioral and physiological traits in insect including geotaxis 36 , circadian phase shifting 37 , 38 and in regulation of ecdysone biosynthesis via G-protein couple receptors and also through extracellular Ca 2+ mediated pathways 39 , 40 . In this context, significant differential regulation of per gene, alteration of circadian rhythm, significant upregulation of extracellular Ca 2+ and guanine nucleotide-binding proteins and positive phototactic response of larvae during tree-top disease may have indicated the possible involvement of PDFs thereby regulating 20-hydroxyecdysone (20E), which was found to be a major inducing factor of tree top disease 16 , 41 .…”
Section: Resultsmentioning
confidence: 99%
“…Instead, the climbing behaviour appeared to be moultingrelated. Using RNAi and exogenous hormone treatment, a recent report showed that 20-hydroxyecdysone (20E), a substrate of EGT, inhibited virus-induced tree-top disease in HearNPVinfected larvae [61]. One possible explanation is that the higher 20E hormone titre may trigger apolysis, leading to an immobilized state of larvae and death at lower positions.…”
Section: (B) Enhanced Locomotory Activity and Virus Disseminationmentioning
confidence: 99%